Coached in the act - Laurie, Victoria (Laurie, Victoria. Life coach mysteries., 2022)
East Hampton life coach Cat Cooper investigates the stabbing of a socialite whose mean-spirited, one-woman show spilled secrets about the area's most eligible bachelors, in the third novel of the series following To Coach a Killer.